Individualized lung recruitment maneuver guided by pulse‐oximetry in anesthetized patients undergoing laparoscopy: a feasibility study. Issue 5 (29th January 2018) - Ferrando, C.; Tusman, G.; Suarez‐Sipmann, F.; León, I.; Pozo, N.; Carbonell, J.; Puig, J.; Pastor, E.; Gracia, E.; Gutiérrez, A.; Aguilar, G.; Belda, F. J.; et al.
Abstract : Background: We conducted this study to test whether pulse‐oximetry hemoglobin saturation (SpO2 ) can personalize the implementation of an open‐lung approach during laparoscopy. Thirty patients with SpO2 ≥ 97% on room‐air before anesthesia were studied. After anesthesia and capnoperitoneum the FIO2 was reduced to 0.21. Those patients whose SpO2 decreased below 97% – an indication of shunt related to atelectasis – completed the following phases: (1) First recruitment maneuver (RM), until reaching lung′s opening pressure, defined as the inspiratory pressure level yielding a SpO2 ≥ 97%; (2) decremental positive end‐expiratory (PEEP) titration trial until reaching lung′s closing pressure defined as the PEEP level yielding a SpO2 < 97%; (3) second RM and, (4) ongoing ventilation with PEEP adjusted above the detected closing pressure. Results: When breathing air, in 24 of 30 patients SpO2 was < 97%, PaO2 /FIO2 ˂ 53.3 kPa and negative end‐expiratory transpulmonary pressure (PTP‐EE ). The mean (SD) opening pressures were found at 40 (5) and 33 (4) cmH2 O during the first and second RM, respectively ( P < 0.001; 95% CI: 3.2–7.7). The closing pressure was found at 11 (5) cmH2 O. This SpO2 ‐guided approach increased PTP‐EE (from −6.4 to 1.2 cmH2 O, P < 0.001) and PaO2 /FIO2 (from 30.3 to 58.1 kPa, P < 0.001) while decreased driving pressure (from 18 to 10 cmH2 O, P < 0.001). SpO2 discriminated the lung's opening and closing pressures with accuracy taking the reference parameter PTP‐EE (area under the receiver‐operating‐curve of 0.89, 95% CI: 0.80–0.99). Conclusion: The non‐invasive SpO2 monitoring can help to individualize an open‐lung approach, including all involved steps, from the identification of those patients who can benefit from recruitment, the identification of opening and closing pressures to the subsequent monitoring of an open‐lung condition.